Changes of corneal epithelial thickness before and after OK-correction according to SD-OCT - S. V. Milash; E. P. Tarutta (Российский офтальмологический журнал, 2018)
Purpose: to evaluate the thickness of corneal epithelium after orthokeratological (OK) correction with the help of SDOCT. Material and methods: 18 patients (36 eyes) averagely aged 12.11 ± 1.68 with myopia of -3.21 ± 0.94 D and axial length of 24.47 ± 0.7 mm were examined. All patients were checked for corneal epithelial thickness (ET) with the help of SD-OCT Avanti RTVueXR (Optovue Inc., Fremont, CA, USA), which created maps of 6 mm in diameter before OK correction with lenses ESA-DL (Dr. Lens Technology, Russia) and 36.44 ± 5.81 days after it. A corneal ET map was divided into 17 sectors with average values indicated, and 3 zones (the central zone of 2 mm, the paracentral zone from 2 to 5 mm, and the mid-peripheral zone from 5 to 6 mm). We calculated the maximum (Max) and the minimum (Min) values of ET, the difference between them (Max Min) in the 5 mm zone, and standard deviation of values in the 5 mm zone (Std Dev). Results. The corneal ET showed no difference among the sectors of the 6-mm map (p > 0.05) before OK lenses were worn. The ET in the central zone was 53.1 ± 1.68 μm. The ET in the central zone decreased by 16.6 % from the initial value after 36.44 ± 5.81 days of OK correction, with a single sector (S) showing a statistically significant difference in the paracentral zone. In the mid-peripheral zone, the ET increased by 14.1 % from the reference. Max and Min ET, and Max-Min Std Dev in the 5-mm zone differed significantly after OK correction (p < 0.05). Conclusion. After OK correction, the ET significantly decreases in the central zone and increases in the mid-peripheral zone. These changes account for the flattening of the anterior corneal surface and contribute to the refractive effect of OK lenses. For citations: Milash S.V., Tarutta E.P. Changes of corneal epithelial thickness before and after OK-correction according to SD-OCT. Russian ophthalmological journal. 2017; 10 (3): 49-54. doi: 10.21516/2072-0076-2017-10-3-49-54 (in Russian).